Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
IEEE Local Computer Network Conference 2010
DOI: 10.1109/lcn.2010.5735771
|View full text |Cite
|
Sign up to set email alerts
|

Bag-of-Tasks applications scheduling on volunteer desktop grids with adaptive information dissemination

Abstract: In this paper, we explore the problem of scheduling multiple concurrent Bag-of-Tasks (BoT) applications in unstructured peer-to-peer (P2P) volunteer desktop grids built around a super-peer framework. Resource availability information is exchanged among the super-peers using a light-weight thresholddriven gossip protocol with the aim of minimizing the resource discovery overhead. We present a comprehensive study of the properties of fixed threshold and adaptive threshold based gossiping mechanisms using detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The tasks travel from the root to the leaves, using decisions taken in each step. The decision could be based on probabilistic models [Kwan and Jogesh 2010] or other factors, such as reputation [Rius et al 2012].…”
Section: Related Workmentioning
confidence: 99%
“…The tasks travel from the root to the leaves, using decisions taken in each step. The decision could be based on probabilistic models [Kwan and Jogesh 2010] or other factors, such as reputation [Rius et al 2012].…”
Section: Related Workmentioning
confidence: 99%
“…In [32], we observed that superpeers could resolve real-world queries with relatively high hit rate under moderate overhead. Advertising cost can be further reduced by advertising only the aggregate information about resources indexed at a superpeer [30], e.g., total number of CPU cores or total processing capacity (measured in FLOPS) of all the peers assigned to a superpeer. Though such aggregated attribute values are acceptable for desktop grids and bag-of-task applications [30], they are too abstract for latency sensitive applications such as CASA, mobile social networks, and P2P clouds where performance is determined by the interactions among dynamic and individual resources.…”
Section: Unstructured-overlay-based Solutionsmentioning
confidence: 99%
“…Gossiping is another form of disseminating resource information in which RSs propagate in the network due to pairwise exchanges of RSs between randomly selected node pairs [30][31]. Multiple concurrent agents are used to speed up the gossiping.…”
Section: Unstructured-overlay-based Solutionsmentioning
confidence: 99%
See 2 more Smart Citations